Effect of HMGB1 gene polymorphisms on AMPK and HMGB1 levels in neonatal sepsis - Orujova, Pusta; Sultanova, Naila; Orujlu, Madina; Guliyeva, Sevda (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Neonatal sepsis is a major cause of morbidity and mortality, influenced not only by infection but also by genetic and immune responses. High Mobility Group Box 1 (HMGB1) acts as a late pro-inflammatory mediator, while AMP-activated protein kinase (AMPK) regulates cellular energy. We examined whether single-nucleotide polymorphisms (SNPs) in the HMGB1 gene affect HMGB1 and AMPK levels in neonates with sepsis.Methods: Ninety-nine neonates were studied: 51 with sepsis, 18 with congenital pneumonia, and 30 healthy controls (34–42 weeks). HMGB1 sequencing identified SNPs (rs3742305/COSV58104338, rs2249825, rs41376448, rs1060348). Plasma HMGB1 and AMPK were measured by ELISA on day 2 of admission. Clinical data (CRP, procalcitonin, blood cultures) were collected. Infants were analyzed by genotype (wild type, heterozygous, homozygous) and cumulative SNP count.Results: SNP frequency was higher in sepsis (52.9%) than in pneumonia (27.8%); homozygous variants occurred only in sepsis (p < 0.05). On day 2, HMGB1 and AMPK were lower in sepsis versus pneumonia (1510 ± 411 vs. 1709 ± 422; 1132 ± 401 vs. 1485 ± 401). For rs3742305, homozygotes had higher HMGB1 and heterozygotes reduced AMPK. For rs2249825, homozygotes showed the highest HMGB1 and lowest AMPK; heterozygotes also had reduced AMPK. Rs41376448 showed a similar pattern, while rs1060348 was not significant. With increasing SNPs (1–4), AMPK declined progressively (p < 0.05), while HMGB1 trended upward.Conclusions: HMGB1 polymorphisms, particularly rs3742305, rs2249825, and rs41376448, are linked to altered HMGB1 and AMPK in neonatal sepsis. The cumulative SNP load predicts greater metabolic dysregulation, suggesting HMGB1 genotyping may aid risk stratification and personalized therapy.